2012
DOI: 10.1021/ol203418u
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Outcomes of Gold(I)-Catalyzed Indole Additions to 3,3-Disubstituted Cyclopropenes

Abstract: Depending on the conditions employed, gold(I)-catalyzed addition of indoles to 3,3-disubstituted cyclopropenes can be controlled to yield either 3-(E)-vinylindoles (3) or bis-indolylalkanes (4). If the cyclopropene substituents are sterically bulky, unprecedented gold-catalyzed oxidation under air occurs to yield bis-indolylalkene (5) and epoxide (6) at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…[31] In 2016 Widenhöfer and co-workers accomplished gold-catalyzed anti-Markovnikov intermolecular hydroarylation of methylenecyclopropanes 14, providing an interesting methodology for the preparation of (cyclopropylmethyl)indoles 15 (Scheme 6). However, their use require strictly controlled reaction conditions, as reported, for example, by Lee for gold-catalyzed addition of indoles to 3,3-disubstituted cyclopropenes.…”
Section: Intermolecular Hydroarylation Of Alkenesmentioning
confidence: 99%
“…[31] In 2016 Widenhöfer and co-workers accomplished gold-catalyzed anti-Markovnikov intermolecular hydroarylation of methylenecyclopropanes 14, providing an interesting methodology for the preparation of (cyclopropylmethyl)indoles 15 (Scheme 6). However, their use require strictly controlled reaction conditions, as reported, for example, by Lee for gold-catalyzed addition of indoles to 3,3-disubstituted cyclopropenes.…”
Section: Intermolecular Hydroarylation Of Alkenesmentioning
confidence: 99%
“…It has been reported that 3,3′‐BIMS can be obtained as by‐products in the reversible acid‐catalysed reaction of indoles with aldehydes, where 3‐vinyl indoles are the major products at low acid‐catalyst loading and at low temperatures . Similarly, gold‐catalysed/acid‐assisted addition of indoles to 3‐vinyl indoles also gives BIMs . In order to investigate the reversibility of the nucleophilic addition of the external indole to the cycle 2‐vinyl indole 4′ , the isolated BIM 3 ai was reacted under platinum conditions with methanol and the external indole 2 a .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, new methodologies employing different metal catalysts in the reaction of indoles and unsaturated precursors have been reported . The most studied reaction is the two‐fold addition of indoles to alkynes catalysed by Au, Ga, Pd, Ru or Cu (Scheme b), but the Au‐catalysed reaction of indoles with cyclopropenes for the synthesis of 3,3′‐BIMs has also been reported (Scheme c) . Metal‐catalysed reactions of indoles with allenes has been widely explored in recent years .…”
Section: Introductionmentioning
confidence: 99%
“…Gold(I)‐catalyzed ring opening of 3,3‐disubstituted cyclopropenes can be used to generate electrophilic species 121 which ensure a proper reaction with indoles (Scheme ) . The intermediate adduct 122 undergoes to a deauration–protonation leading to the alkenylated derivative.…”
Section: Other Alkenylating Reactantsmentioning
confidence: 99%